Rumpelstiltskin - Zelinsky, Paul O. (New York : E.P. Dutton, 1986)
A strange little man helps the miller's daughter spin straw into gold for the king on the condition that she will give him her first-born child.
Booklist
Sch Libr Jnl
Booklist
Booklist
Keywords: Fairy tales; Folklore -- Germany